Comparative Growth Analysis of Crossbred Progenies of Boer Goats in Nepal - Tamang, Dawa Tshiring; Sharma, Mohan Prasad; Devkota, Naba Raj; Bhattarai, Nirajan; Barsila, Sankar Raj (Journal of the Institute of Agriculture and Animal Science, 2024)
Boer breed of goat is renowned for its excellence in meat production, robust body structure, rapid growth and superior carcass quality. A sample of 898 Boer goats from 5 different blood groups were taken from 15, 17 and 19 wards of Bharatpur Metroposis in Chitwan district of Nepal in order to perform comparative analysis among different genetic groups of Boer goats on their productive performance. The collected data were analyzed by using Microsoft Office Excel 2013 and RStudio. Results revealed that the 87.5% Boer goats consistently had exhibited superior growth performances of across multiple parameters indicating a robust genetic foundation inherited from the Boer breed. This was evidence by its highest average litter weight at birth (4.74 ± 0.08), litter weight at weaning (23.40 ± 0.72) and its massive body confirmation in terms of length (L), heart girth (G) and wither height (H). In contrast, bloodlines with lower percentages of Boer genetics such as 37.5% and 50% Boer goats had shown comparatively lower growth performances but showed potential adaptability to extensive grazing conditions. Therefore, these findings suggest systematic cross breeding program that may better focus on specific production targets according to suitable production system and breed in favorable season showing highest genetic performance which could improve the efficiency and sustainability of goat production in similar regions of Nepal.